Guilt-averse or reciprocal? Looking at behavioural motivations in the trust game - Yola Engler; Rudolf Kerschbamer; Lionel Page (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
For the trust game, recent models of belief-dependent motivations make opposite predictions regarding the correlation between back-transfers and second- order beliefs of the trustor: While reciprocity models predict a negative correlation, guilt-aversion models predict a positive one. This paper tests the hypothesis that the inconclusive results in previous studies investigating the reaction of trustees to their beliefs are due to the fact that reciprocity and guilt-aversion are behaviorally relevant for different subgroups and that their impact cancels out in the aggregate. We find little evidence in support of this hypothesis and conclude that type heterogeneity is unlikely to explain previous results.
Keywords: C25; C70; C91; D63; D64; 330